Analysis of The Energy Parameters of Selected Biomass and Biochar Types and the Environmental Impact of Their Ashes - Kujawska, Justyna; Bilicz, Ewelina; Mendyk, Emilia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study determined the similarities and differences between the fuel properties of different types of biomass (triticale and oat straw; bark: oak, alder, hornbeam, pine) and biochar (municipal waste biochar, composting biochar, pellet biochar and Fluid`s biochar). Bulk and actual densities and moisture contents, ash amounts, elemental composition (C, H, N) were determined, and the calorific value, heat of combustion and porosity of the substances studied were calculated.
Keywords: biochar; biomass; energy parameters; environmental impact; biowęgiel; biomasa; parametry energetyczne; wpływ na środowisko